2012
DOI: 10.1542/peds.2011-3575
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Procalcitonin in Well-Appearing Young Febrile Infants

Abstract: Among well-appearing young infants with FWS, PCT performs better than CRP in identifying patients with IBIs and seems to be the best marker for ruling out IBIs. Among patients with normal urine dipstick results and fever of recent onset, PCT remains the most accurate blood test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
80
4
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 23 publications
1
80
4
10
Order By: Relevance
“…We found an AUC for PCT of 0.83 (95%CI: 0.76-0.89) for the 0.5ng/ml cut-off level, which was also the optimal level found. While some studies found lower cut-off levels (6,7,12), permitting a more-limited approach, most of the studies reported a cut-off of 0.5ng/ ml or higher (2,(9)(10)(11)14,15,(31)(32)(33)(34). Even if only modestly, CRP outperformed PCT for prediction of SBI in our study, which agrees with the findings of several other studies (10)(11)(12)15,17,29).…”
Section: Discussionsupporting
confidence: 90%
“…We found an AUC for PCT of 0.83 (95%CI: 0.76-0.89) for the 0.5ng/ml cut-off level, which was also the optimal level found. While some studies found lower cut-off levels (6,7,12), permitting a more-limited approach, most of the studies reported a cut-off of 0.5ng/ ml or higher (2,(9)(10)(11)14,15,(31)(32)(33)(34). Even if only modestly, CRP outperformed PCT for prediction of SBI in our study, which agrees with the findings of several other studies (10)(11)(12)15,17,29).…”
Section: Discussionsupporting
confidence: 90%
“…The figure is even higher in infants with fever of recent onset. [20][21][22][23] According to our results, the bacteremia rate in young infants with UTI is related to general appearance and PCT value. These 2 factors can help identify infants at increased risk of having bacteremia.…”
Section: Discussionmentioning
confidence: 53%
“…[10][11][12][13][14] But not all infant had the same risk of developing an IBI. [15][16][17][18] This is the reason several approaches had been taken, trying to select within febrile infants younger than 90 days old a group of patients with low risk of adverse events, that might be suitable for outpatient management. 19,20 This same approach has been taken for febrile infants with an UTI, 3 with a very good sensitivity and negative predictive value for predicting adverse events, but with a rate of false negatives of almost 23% when predicting bacteremia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the great value of PCT in diagnosis of IBI in febrile infants, 17,22,23 so it seemed necessary to include it in the model.…”
Section: Discussionmentioning
confidence: 99%